The right to die via euthanasia: an expository study of the Shari‘ah and laws in selected jurisdictions - Ansari, Abdul Haseeb; Sambo, A.O.; Abdulkadir, A.B. (American-Eurasian Network for Scientific Information (AENSI), 2012)
The right to die, which prominently includes euthanasia with consent, is one of the issues that have been subject of intense debate over times. It has been a pertinent issue in human rights discourse as it also affects ethical issues pertaining to doctors. The reason is because the right to life, which represents the most significant aspect of human rights, appears to be in conflict with the right to die. It is notable here that right to life does not include right to die. The paper analyses the development, types and the legal and ethical debates concerning both the types of euthanasia. From there, it makes an expository study of the concept in the Shari‘ah and in selected jurisdictions, and suggests that euthanasia should be allowed only in exceptional situations. While deciding on formulating a law prescribing these exceptional situations and enforcing the law, all aspects of euthanasia – medical, social, economic, ethical and legal – have to be taken into consideration. Law should have punitive measures for preventing misuse of the law. Key words: Right to die, Euthanasia, Right to life, Life support system, Human rights